P673 Trends in inflammatory bowel disease infections and vaccinations in the past four decades - a high-level text mining analysis of PubMed publications. (21st January 2022) - Lahat, A; Klang, E
Abstract: Background: Many therapeutic options for inflammatory bowel disease emerged during the last decades, along with the rise in disease prevalence and incidence. These new treatments exposed patients to various potential infections and promoted pre-treatment screening and vaccination. We aimed at assessing the published literature on different prophylactic screening and vaccination options in that period. Special attention was attributed to latest data assessing covid-19 vaccinations. Methods: We have queried PubMed for all available IBD-related entries published during 2000–2020. The following data were extracted for each entry: PubMed unique article ID (PMID), title, publishing journal, abstract text, keywords (if any), and authors' affiliations. Two gastrointestinal specialists decided in consensus on a list of terms to classify entries. The terms belonged to four groups: Opportunistic Infections, prophylactic screening, prophylactic vaccinations/treatment, regular vaccines. Annual trends of publications for the years 1980–2020 were plotted for different screening, vaccinations, and infections types. The slopes of publication trends were calculated by fitting regression lines to the annual number of publications. Results: Overall, 98, 339 IBD entries were published between 1980 and 2020. Of those, 10, 128 entries belonged to one of the four investigated groups. Entries concerning opportunistic infections showed the sharpest rise, with 22 entries and 1980 to 623 entries in 2020 (slope 3.6, p<0.001). Entries concerning prophylactic screening rose from 10 entries in 1980 to 204 entries in 2020 (slope 1.4, p<0.001). Both entries concerning prophylactic vaccinations/treatments and regular vaccines did not show a significant rise (slope 0.08, and slope 0.22, respectively). Publications' trend is shown in figure 1. Figure 1- publication trends of vaccines and opportunistic infections in IBD patients during the past four decades During COVID 19 pandemic a total of 44 publications were identified. Of them. 37 were relevant to vaccines and immune reaction. 19 publications (51%) were guidelines/recommendations, 14 (38%) assessed immune reaction to vaccination, most of them (11, 61%) to mRNA vaccines. Results are shown in figure 2. Figure2- publication trends of COVID 19 vaccines during the pandemic Conclusion: According to publications trend analysis, during the past two decades, publications regarding opportunistic infections and prophylactic screening increased stteply compared to the two decades during pre- biologic area. During COVID -19 pandemic most publications included vaccinations' recommendations and guidelines, and only 38% included real-world data assessing reaction to vaccinations. More research is needed.